Analisis Karakteristik Pasang-Surut Menggunakan Metode Kuadrat Terkecil (Studi Kasus: Dermaga Sunda, Pondok Dayung, Jakarta Utara) - Adriansyah, Abdul Hadi; Laksmi, Anasya Arsita; Christy, Abigail; Sitorus, Andreas Robert Panogu; Kampai, Arya Maulana; Putra, Dewa Ramadhan Astama; Fauzah, Dewi (Universitas Ibn Khaldun, 2024)
Indonesia is an archipelago state with 17.504 islands and an ocean area is 3,2 million square kilometers. Indonesia has challenges in maintaining maritime defense around its archipelago. Naval bases not only act as command and control centers for sea defense operations but also as providers of berthing facilities for Indonesian Warships (KRI). Navy base operations depend on oceanographic conditions, including tides. This research aims to analyze the tidal characteristics, in the form of harmonic components, tidal types, and tidal forecasting. In the analysis, the least squares method is used which provides high accuracy and precision to the research output. The results showed a Formzahl number 4,997; that the waters at Pondok Dayung have a diurnal tidal type, with the phenomenon of one high tide and one low tide in one day. The mean sea level is 60,07 cm with a tidal ridge is 127,20 cm, where the highest level is 121,96 cm and the lowest level is -5,24 cm.